Prognostic value of myopic disk deformation in myopic choroidal neovascularization: A 6-year follow-up study - Han, Ye Eun; Kim, Yoon Jeon; Yang, Hyun Seung; Moon, Byung Gill; Lee, Joo Yong; Kim, June-Gone; Yoon, Young Hee (Frontiers in Medicine, 2022)
Purpose: To evaluate the clinical characteristics of myopic choroidal neovascularization (mCNV) according to peripapillary atrophy (PPA) and optic disc tilt and to explore whether those myopic disc deformations are associated with the prognosis of myopic CNV. Methods: Patients with subfoveal mCNV who received intravitreal bevacizumab injection and followed for ≥ 3 years were included. PPA was quantified as area of the ß-zone PPA /disc area ratio (PDR) and optic disc tilt as the tilt ratio (the longest/shortest disc diameter). We compared the clinical characteristics in terms of PDR and tilt ratio and identified the poor prognostic factors using Cox proportional hazard model. Results: Among 80 eyes of 80 patients, 29 (36.30%) eyes developed macular atrophy during 80.71 ± 34.76 months. PDR and tilt ratio are strongly correlated with each other (P=0.004). Higher PDR showed significant correlations with longer axial length (P=0.013), worse baseline and final VA (P=0.007 and P=0.047), and thinner subfoveal choroidal thickness (P=0.039), while higher tilt ratio showed significant correlations only with longer axial length (P=0.036). High PDR was also an independent risk factor for both macular atrophy (OR=2.257, P<0.001) and poor visual outcome (HR=1.174, P=0.007), while high disc tilt ratio was not. Conclusion: Subfoveal mCNV with higher ß-zone PPA area/disc area ratio had worse functional and structural outcomes.